Measuring the T‐cell down‐regulation of TCR‐zeta, ZAP‐70 and CD28 in arthritis patients: An old tool for new biomarkers. Issue 12 (22nd August 2019) - Zizzo, Gaetano; De Santis, Maria; Bosello, Silvia; Tolusso, Barbara; Alivernini, Stefano; De Luca, Giacomo; Gremese, Elisa; Ferraccioli, Gianfranco
Abstract: Low T‐cell receptor (TCR)/CD28 signaling lymphocytes are expanded in arthritis. We asked whether the down‐expression of TCR‐related molecules correlates with specific arthritis characteristics and if it has clinical implications. TCR‐ZETA, ZAP‐70 and CD28 expression was measured by flow cytometry in synovial fluid (SF) and peripheral blood (PB)‐derived T cells. In PB, ZETA‐downregulation in CD4 + CD28 + and consequent CD4 + CD28lowZETAlow cell expansion correlate with CRP elevation, leukocyte recruitment into SF and, primarily, disease activity (DAS). In some patients, ZETA‐downregulation extends to CD8 + CD28null and/or CD8 + CD28 + cells, and this correlates with enhanced leukocyte recruitment, multiple joint involvement, and disability index (HAQ). ZETA‐downregulation in CD4 + CD28 + may also lead to CD4 + CD28 + ZETAnull cell expansion, which strongly correlates with HAQ. In SF, ZETA‐downregulation in CD8 + CD28null and consequent CD8 + CD28nullZETAlow/null cell expansion correlate with CRP elevation and neutrophilic influx into SF, whereas ZAP‐downregulation in CD8 + CD28 + and consequent CD8 + CD28lowZAPlow cell expansion strongly correlate with HAQ and DAS. ZETA‐downregulation is preponderant in SF of seronegative arthritides, with seronegative rheumatoid arthritis showing significant down‐regulation in CD8 + CD28null, and non‐rheumatoid arthritides showing significant down‐regulation in CD4 + CD28 + . Altogether, we identified new molecular and cellular biomarkers of arthritis‐related T‐cell inflammation, useful for assessing arthritis activity, predicting polyarticular progression and functional impairment, characterizing seronegative arthritides, and possibly tailoring immunotherapies. Abstract : Down‐regulation of CD28, TCR‐zeta (TCR‐ζ) and/or ZAP‐70 in circulating and synovial fluid‐derived T cells of arthritis patients is associated with discrete arthritis characteristics. Measuring the expansion of certain down‐regulated T‐cell phenotypes may provide useful information about inflammation and disease activity, polyarticular progression and disability, differential diagnosis and response to treatment.